Obstructive sleep apnea (OSA) and reaction time in commercial vehicle drivers- an exploratory study. (March 2021) - Kamalesh, R.; Krishnakumar, M.; Mathangi, D.C.
Abstract: Context: Road traffic accidents [RTA] are a major cause of morbidity and mortality in India. Obstructive sleep apnea [OSA] has been identified world over as one of the risk factors in vehicle collisions. The estimated death due to RTA attributable to OSA is largely unknown. Aim: Aim of the study was to estimate the risk of OSA in commercial drivers and see the relationship with reaction times. Setting and Design: Prospective exploratory study in a metropolitan city. Method: Commercial vehicle drivers with a minimum of 5 years driving experience were administered STOPBANG questionnaire for identification of risk of OSA. Driving history and details related to collisions were elicited using a questionnaire. Anthropometric measures, visual and auditory reaction times were assessed. Results: Based on the questionnaire, 35% of the drivers were at risk for OSA. Drivers with high risk of OSA showed reduced auditory reaction time. Anthropometric measurements of the drivers with risk of OSA were significantly higher from those without OSA. There was no significant correlation between OSA and collisions. Conclusion: Prevalence of risk for OSA is high among commercial vehicle drivers, however it not the single risk factor contributing to collisions. OSA along with reduced reaction time could probably increases the risk of vehicular collisions.